363 A Comparative Analysis of Night-Time General Surgical Training. (19th August 2022) - Aseem, R; Khan, N; Bowbrick, G
Abstract: Aim: The aim of surgical training is to ensure trainees acquire competencies to perform as a Day 1 Consultant. The last decade has seen the introduction of European Working Time Directive, NELA guidelines and the revised Junior Doctor Contract. All of these, as well as the COVID 19 pandemic, have caused concerns regarding training. Our aim was to examine any changes to night-time on call activity during this time. Method: We retrospectively analysed prospectively collected data from 2011, 2018, and 2021, in a busy District General Hospital. The data collection period was 31 days, looking at night-time (8pm to 8am) operative experience, supervision, and non-operative activity. A regression analysis was conducted to compare outcomes. A qualitative survey was used to assess attitudes and confidence. Results: On average, trainees spent 11% of their time operating independently, 2% operating supervised, 11% attending trauma-calls and 73% clerking/non-educational activities. There was a significant difference between the hours spent on operative versus non-operative activity (P 0.00046) with no differences over the years. Junior trainees did not feel confident operating at night and only 33% of all trainees found night-time training effective. Conclusions: Nightshifts comprise a substantial proportion of potential training opportunities and managing the unselected emergency take is one of the Capabilities in Practice. Effective solutions must be implemented to help improve night-time surgical experience and confidence in order for this time to be effective for training of both operative and non-operative competency attainment.